Appraisal of Potato Production Practices in the Adamawa and West regions of Cameroon. Baseline Survey Report - Adamu, I.; Harahagazwe, D.; Fornkwa, V.; Apan, A.; Tiozang, E.; Parker, M. (International Potato Center, 2021)
We conducted a baseline survey to appraise the current potato practices and farming systems in the Adamawa and West regions of Cameroon where a GIZ-funded project (ONE WORLD – No Hunger, or SEWOH) titled "Green Innovation Centers for the Agricultural and Food Sector" (ProCISA) is being implemented. We employed a mix of qualitative and quantitative methods to gather and analyze data/information. This study focused on potato farmers that have been into potato production for at least two years. We developed a structured questionnaire which was administered to small- and medium-sized potato growers based on a literature review and consultation with key stakeholders. The questionnaire was pretested through ten in-depth interviews with selected farmers in the Adamawa and West regions. Local enumerators were recruited in each region and trained to administer the questionnaire in the field. In total, 341 questionnaires were completed (141 in Adamawa and 200 in the West region) in 133 villages (35 in Adamawa and 98 in the West region) using a modified systematic random sampling technique to ensure even representation. The collected data was then coded and analyzed. Farmers in both regions cultivate an area typically not more than 1 hectare (ha), but in Adamawa, farmers grow only one round of potatoes, while in the West they cultivate two in a year (i.e., during the rainy season from March to October). Top challenges to farmers in our survey area include low access to quality seed, poor management and agronomic practices, and limited access to credit, fertilizers and pesticides. In Adamawa, just over half of the farmers (51%) reported having received no agricultural training in the past, compared to just 43% in the West region. Thus, interest in and willingness to participate in future trainings are high.